WHO guidelines for a healthy diet and mortality from cardiovascular disease in European and American elderly: the CHANCES project - Jankovic, Nicole; Geelen, Anouk; Streppel, Martinette T; de Groot, Lisette Cpgm; Kiefte-de Jong, Jessica C; Orfanos, Philippos; Bamia, Christina; Trichopoulou, Antonia; Boffetta, Paolo; Bobak, Martin; Pikhart, Hynek; Kee, Frank; et al. (The American journal of clinical nutrition, 2015)
BACKGROUND: Cardiovascular disease (CVD) represents a leading cause of mortality worldwide, especially in the elderly. Lowering the number of CVD deaths requires preventive strategies targeted on the elderly. OBJECTIVE: The objective was to generate evidence on the association between WHO dietary recommendations and mortality from CVD, coronary artery disease (CAD), and stroke in the elderly aged ≥60 y. DESIGN: We analyzed data from 10 prospective cohort studies from Europe and the United States comprising a total sample of 281,874 men and women free from chronic diseases at baseline. Components of the Healthy Diet Indicator (HDI) included saturated fatty acids, polyunsaturated fatty acids, mono- and disaccharides, protein, cholesterol, dietary fiber, and fruit and vegetables. Cohort-specific HRs adjusted for sex, education, smoking, physical activity, and energy and alcohol intakes were pooled by using a random-effects model. RESULTS: During 3,322,768 person-years of follow-up, 12,492 people died of CVD. An increase of 10 HDI points (complete adherence to an additional WHO guideline) was, on average, not associated with CVD mortality (HR: 0.94; 95% CI: 0.86, 1.03), CAD mortality (HR: 0.99; 95% CI: 0.85, 1.14), or stroke mortality (HR: 0.95; 95% CI: 0.88, 1.03). However, after stratification of the data by geographic region, adherence to the HDI was associated with reduced CVD mortality in the southern European cohorts (HR: 0.87; 95% CI: 0.79, 0.96; I(2) = 0%) and in the US cohort (HR: 0.85; 95% CI: 0.83, 0.87; I(2) = not applicable). CONCLUSION: Overall, greater adherence to the WHO dietary guidelines was not significantly associated with CVD mortality, but the results varied across regions. Clear inverse associations were observed in elderly populations in southern Europe and the United States.
Keywords: Nutrition Policy; mastné kyseliny; Nutrition Assessment; dietní proteiny; Europe; Female; etnicita; Vegetables; Dietary Fiber; Ethnicity; cardiovascular disease; Fatty Acids; ženské pohlaví; Patient Compliance; CHANCES; zelenina; Dietary Proteins; lidé; Evropa; cohort; World Health Organization; Fatty Acids, Unsaturated; Fruit; cholesterol dietní; výživová politika; adherence pacienta; Světová zdravotnická organizace; dieta; ovoce; Middle Aged; prospektivní studie; Spojené státy americké; Diet; Male; Cardiovascular Diseases; Aged; Prospective Studies; nenasycené mastné kyseliny; Meta-Analysis as Topic; meta-analysis; United States; kardiovaskulární nemoci; chronická nemoc; lidé středního věku; hodnocení stavu výživy; senioři; mužské pohlaví; Dietary Carbohydrates; Cholesterol, Dietary; dietní sacharidy; Chronic Disease; metaanalýza jako téma; potravní vláknina; aging; Humans